2020
DOI: 10.3389/fimmu.2019.03151
|View full text |Cite
|
Sign up to set email alerts
|

Major Histocompatibility Complex Binding, Eluted Ligands, and Immunogenicity: Benchmark Testing and Predictions

Abstract: Antidrug antibody (ADA) responses impact drug safety, potency, and efficacy. It is generally assumed that ADA responses are associated with human leukocyte antigen (HLA) class II-restricted CD4+ T-cell reactivity. Although this review does not address ADA responses per se, the analysis presented here is relevant to the topic, because measuring or predicting CD4+ T-cell reactivity is a common strategy to address ADA and immunogenicity concerns. Because human CD4+ T-cell reactivity relies on the recognition of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
2

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 34 publications
1
20
0
Order By: Relevance
“…These studies suggested that 1,000 nM is a generally applicable threshold for biologically relevant binding in the context of HLA class II. This threshold was also confirmed in a recent analysis which found that 83.3% of HLA class II restricted epitopes are predicted to bind their corresponding restricting allele with an affinity of 1,000 nM, or better (19). Of note, optimal thresholds for MHC class II are still unclear and are being discussed in the community.…”
Section: Hla Class II Reported Eluted Ligands Are In General Predicsupporting
confidence: 52%
See 1 more Smart Citation
“…These studies suggested that 1,000 nM is a generally applicable threshold for biologically relevant binding in the context of HLA class II. This threshold was also confirmed in a recent analysis which found that 83.3% of HLA class II restricted epitopes are predicted to bind their corresponding restricting allele with an affinity of 1,000 nM, or better (19). Of note, optimal thresholds for MHC class II are still unclear and are being discussed in the community.…”
Section: Hla Class II Reported Eluted Ligands Are In General Predicsupporting
confidence: 52%
“…Peptides with predicted binding affinities of >1,000nM were considered predicted nonbinders. This threshold was selected based on previous studies analyzing the binding affinity of HLA class II restricted T cell epitopes (16)(17)(18)(19).…”
Section: Hla Binding Predictionsmentioning
confidence: 99%
“…Peptides with predicted percentile ranks of >20% were considered predicted non‐binders. This threshold was selected based on previous studies analysing the binding affinity of HLA class II‐restricted T‐cell epitopes 20‐23 …”
Section: Methodsmentioning
confidence: 99%
“…Overall, the 49 most dominant epitopes showed significantly higher binding promiscuity (number of alleles bound at the 1,000 nM or better threshold) (Paul et al, 2019;Southwood et al, 1998) for the panel of common HLA class II than a control group of 49 non-epitopes derived from the same proteins (Average number of HLA predicted to be bind ± SD epitopes = 10.8 ± 6.5; non-epitopes = 5.7 ± 6; p=0.0001 by Mann-Whitney; Fig. S3C-D).…”
Section: Hla Binding Capacity Of Dominant Epitopesmentioning
confidence: 99%